Quantitative Assessment of Cost and Time Implication of Susceptibility of Building Elements to Variation in Nigeria - Babatunde, Solomon Olusola (International Journal of Sustainable Construction Engineering and Technology, 2013)
A number of research studies have been carried out on the causes and effects of variation on construction project delivery, thereby taking for granted the susceptibility of building elements to variations. This formed the basis of this paper with a view to assessing the cost and time implications of the susceptibility of each building element to variation during construction process in Nigeria. Archival record comprises contract drawings, original bill of quantities, addendum and reduction bill of quantities, and minutes of site meetings among others were used to extract data relating to initial cost, final construction cost, estimated period, final completion period of each building element attributed to variations. The data obtained were analyzed using statistical methods of average, percentage, regression analysis, and analysis of variance (ANOVA). The study identified the building elements having greater than 20% of cost overrun due to variation as earthwork and fillings, frame, windows and external doors, fittings and furnishings, water installation, and external services. The study further identified the building elements having greater than 25% time overrun due to variation as earthwork and fillings, block work (at substructure), upper floors, external walls, wall finishing among others. The results of ANOVA and regression analysis on the building elements cost and time were used to establish models. Thus, the established models are: AFC= 981690 + 1.033AIC; and AFCO= 608390.865 +1.310AIC to predict the average final cost of each building element, and the average final cost overrun of each building element due to variation respectively, where AFC= Average Final Cost, AIC= Average Initial Cost, and AFCO= Average Final Cost Overrun. Also, the study established the model: Y = 1.379(X) – 0.251 for predicting the average actual completion period of each building element, where Y= Average Actual Completion Period, and X= Average Estimated Period (week). The study provides information that enables the clients, consultants/professionals, and other construction stakeholders to understand the building elements that demands specific attention in terms of cost and time implications of variations. The study also provides building clients a foreknowledge of cost variance that is likely to occur on each building element during construction process